Infrastructure of innovative system as a factor of transformation of industrial structures - Bal-Woźniak, Teresa (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
It is proved in the article that identification and shaping of infrastructure of innovative system has contemporarily the fundamental meaning for transformation of industrial structures. Thus the pace of changes and effects of performed reindustrialization are determined by such infrastructure elements as: enterprise, competence, group activity and internal communication, organizational solutions together with computer support and network of external connections. This work is devoted to the characteristics of the mentioned elements.